The Politics of Historical Memory and Commemoration in Africa - Mark-Thiesen, Cassandra; Mihatsch, Moritz; Sikes, Michelle (2021)
The volume re-centres Africa and African history in memory studies, with each chapter drawing parallels to comparable cases in Africa and the world. An underlying assumption is that what can be learned from the politics of historical memory in Africa will have relevance for contemporary politics globally and for understanding how memories can be mobilised for political ends.